(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
Poly (methyl methacrylate)/poly (ethylene oxide) (PMMA/PEO) blend microspheres were prepared by solvent evaporation technique using poly (vinyl alcohol) (PVA) as a stabilizer. Nimesulide, an arthritis drug was successfully loaded into these microspheres. The effect of experimental variables such as ratio of ploy (methyl methacrylate) to poly (ethylene oxide) on nimesulide encapsulation efficiency, release rate, size, and morphology of the microspheres has been investigated. Nimesulide loaded microspheres were analyzed using Fourier transform infrared (FTIR), differential scanning calorimetry (DSC), Xâ€ray diffraction (Xâ€RD), and scanning electron micrograph (SEM). FTIR spectroscopy was used to explain the blending of polymers. DSC and Xâ€RD techniques were used to investigate the crystalline nature of the drug after encapsulation. DSC and Xâ€RD results indicated a nonuniform dispersion of nimesulide in the PMMA/PEO blend matrix.SEMs indicated the formation of spherical microspheres with distinct size. Nimesulide was successfully encapsulated up to 85% in the polymeric matrices. In vitro dissolution experiments performed in pH 7.4 buffer medium indicated a controlled release of nimesulide from blend microspheres up to 12 h.